2008
DOI: 10.1158/0008-5472.can-08-0334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cancer Tests of 1,3-Butadiene Using Internal Dose, Genotoxic Potency, and a Multiplicative Risk Model

Abstract: In cancer tests with 1,3-butadiene (BD), the mouse is much more sensitive than the rat. This is considered to be related to the metabolism of BD to the epoxide metabolites, 1,2-epoxy-3-butene (EB), 1,2:3,4-diepoxybutane, and 1,2-epoxy-3,4-butanediol. This study evaluates whether the large difference in outcome in cancer tests with BD could be predicted quantitatively on the basis of the concentration over time in blood (AUC) of the epoxide metabolites, their mutagenic potency, and a multiplicative cancer risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…It has been shown in both human and animal models that VCM is able to induce liver angiosarcoma and HCC [98][99][100][101][102][103][104] . Maroni et al [105] reported the hepatotoxicity of VCM and other studies have shown the capacity of VCM to Group 1 [76] TCE 79-01-6 Dry cleaning; paint stripping; metal degreasing; production of chlorinated chemical compounds; shoe manufacturing; aircraft/aerospace, electronics and printing industry [125,127] Group 1 [129] PCE 127-18-4 Dry cleaning; textile processing; metal degreasing [138] Group 2A [129] DDT 50-29-3 Farming industry [141,145] Group 2B [148] N-nitrosamines 35576-91-1 Plastic, rubber and pharmacological manufacturing; farming industry; metalworking; electrical component production and use; gasoline and lubricant additives, production and use [159][160][161][162][163][164][165] Group [160,161] TCDD 1746-01-6 Waste management; paper mill; timber manufacturing; iron and steel manufacturing; electric power industry [175,179] Group 1 [76] PeCDF 57117-31-4 Cement and metalworking industry; chemical manufacturing [171,172,175] Group 1 [76] PCB 1336-36-3 Electrical industry, plastic and chemical industry; maintenance/repair technicians of PCB devices [175,[186][187][188][189][190] 1 Group …”
Section: Organic Solventsmentioning
confidence: 99%
“…It has been shown in both human and animal models that VCM is able to induce liver angiosarcoma and HCC [98][99][100][101][102][103][104] . Maroni et al [105] reported the hepatotoxicity of VCM and other studies have shown the capacity of VCM to Group 1 [76] TCE 79-01-6 Dry cleaning; paint stripping; metal degreasing; production of chlorinated chemical compounds; shoe manufacturing; aircraft/aerospace, electronics and printing industry [125,127] Group 1 [129] PCE 127-18-4 Dry cleaning; textile processing; metal degreasing [138] Group 2A [129] DDT 50-29-3 Farming industry [141,145] Group 2B [148] N-nitrosamines 35576-91-1 Plastic, rubber and pharmacological manufacturing; farming industry; metalworking; electrical component production and use; gasoline and lubricant additives, production and use [159][160][161][162][163][164][165] Group [160,161] TCDD 1746-01-6 Waste management; paper mill; timber manufacturing; iron and steel manufacturing; electric power industry [175,179] Group 1 [76] PeCDF 57117-31-4 Cement and metalworking industry; chemical manufacturing [171,172,175] Group 1 [76] PCB 1336-36-3 Electrical industry, plastic and chemical industry; maintenance/repair technicians of PCB devices [175,[186][187][188][189][190] 1 Group …”
Section: Organic Solventsmentioning
confidence: 99%
“…All three metabolites are genotoxic, carcinogenic, and mutagenic and induce chromosomal aberrations, micronucleus formation, sister chromatid exchanges, and mutations in various animal and human cells [7][8][9][10]. While these effects may explain or account for the toxicity and carcinogenicity of BD [8,11,12], detailed biochemical and molecular mechanisms for the toxicity of BD and its metabolites are not completely understood [13,14], and more studies are needed. DEB, the most potent of the three BD metabolites, is a bifunctional DNA alkylating agent that generates reactive oxygen species and exhibits cytotoxic properties [15].…”
Section: Introductionmentioning
confidence: 99%
“…The total genotoxic dose from the epoxide metabolites of BD can be obtained by converting the AUCs of the metabolites in relation to their respective relative mutagenic potency (Fred et al, 2008). With EB as a reference, we previously estimated the relative mutagenic potency per AUC of BD epoxides by using data from mutation studies in hprt loci; for EB, DEB and EBdiol, the relative mutagenic potency per μM · h was estimated to be 1, 32 and 0.21, respectively (Fred et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, the in vivo doses (or AUCs) of the BD epoxy-metabolites were calculated from Hb adduct levels as measured in BD-exposed mice and rats (which was somewhat refined in comparison with our earlier work (Fred et al, 2008)), and humans, as outlined below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation